SOSIALISASI ETIKA BERINTERNET DAN PENINGKATAN LITERASI KEAMANAN DIGITAL SISWA TEKNIK KOMPUTER JARINGAN SMK BAKTI PURWOKERTO - Galih Ragil Fiqriansyah; Daffa Fasyal Pratama; Fauzan Zikrian; Joko Sasongko (Jurnal Padamu Negeri, 2026)
In an effort to raise awareness and understanding among students about safe and responsible internet use, a training session themed ‘Digital Information Security and Internet Ethics’ was held on 30 October 2025 at SMK Bakti Purwokerto with the aim of improving digital literacy among 30 students majoring in Computer and Network Engineering (TKJ). The low level of students' understanding of personal data protection was the main reason for the importance of this activity. The methods employed combined theoretical instruction on digital ethics (netiquette) with practical exercises, including the ‘Password Monster’ strategy and data breach checks via an online platform. Evaluation results showed a significant improvement in students' technical skills and critical awareness regarding personal account security. Thus, this interactive training proved effective in shifting students' paradigms towards becoming smart and responsible internet users.